The Effect of Using Articaine Versus Lidocaine for Inferior Alveolar Nerve Block on Pain After Root Canal Treatment: A Prospective, Randomized Clinical Study - Ali Ghazalgoo; Masoud Saatchi; Saber Khazaei; Elham Shadmehr (Wolters Kluwer Medknow Publications, 2018)
Introduction: The control of pain associated with root canal treatment (RCT) is crucially important in endodontics. The aim of the present study was to compare the effect of using articaine versus lidocaine local anesthetics for inferior alveolar nerve block (IANB) on pain after RCT. Materials and Methods: Eighty-eight patients diagnosed with symptomatic irreversible pulpitis of a mandibular first molar were selected. The patients randomly received either a cartridge of lidocaine or articaine using IANB. RCT was initiated 15 min after the injection. Lip numbness was a requisite for all the patients. The post-operative pain was assessed by using 170-mm visual analog scale at 0, 2, 4, 6, 12, 18, 36, and 48 h after the treatment. The data were analyzed by SPSS 22 statistical software. Results: The mean total post-treatment pain in the lidocaine group was 37.1 ± 32.9 whereas it was 25.4 ± 26.4 for articaine group (P < 0.001). Pain at 4, 6, 12, 18, and 24 h after the RCT in articaine group was significantly less than the lidocaine group (P < 0.001). Conclusion: Using articaine for IANB may increase post-RCT comfort than lidocaine. Further study is needed to confirm the results.